OFDM PAPR Reduction Using Recurring SLM with Cyclic and Linear Block Codes Schemes - Pratima Manhas; M.K Soni (Institute of Advanced Engineering and Science, 2015)
Orthogonal Frequency division multiplexing is a type of multicarrier modulation technique which is used in various wireless & telecommunication standards. In OFDM, higher data rate is split into several narrowband data stream that is transmitted simultaneously over a number of subcarriers. One major disadvantage of using OFDM is high Peak to Average power ratio. This paper presents the simulation result which compares the PAPR using SLM with Cyclic & Linear block codes. The simulation study verifies that the PAPR reduction by proposed method is better than the existing technique (SLM).